Top Rated or Best Seller? Cultural Differences in Responses to Attitudinal versus Behavioral Consensus Cues - Barnes, Aaron J; Shavitt, Sharon (Journal of Consumer Research, 2024)
Abstract Marketers commonly use consensus cues about others’ behavioral choices (“best seller”) or their attitudes (“top rated”) when labeling products. This article suggests that the effectiveness of these types of cues may differ across cultures in ways that carry implications for marketing practice. Prior research shows that in contexts that give rise to an interdependent cultural self-construal, choices are often responsive to social expectations rather than personal preferences. We propose that, because interdependents expect such behavioral conformity, cues that convey consensus about others’ choices may be less diagnostic and, thus, less persuasive than cues that convey consensus about others’ attitudes. Five studies examining cultural self-construal in multiple ways, along with two cross-national industry datasets, offer evidence consistent with this reasoning, suggesting that, among interdependents, behavioral consensus cues can actually be less effective than attitudinal ones, reducing persuasion and willingness to pay. However, among independents, because attitudes are assumed to influence behavioral choices, whether the consensus cue is attitudinal or behavioral makes little difference.